The effect of performance pressure and error-feedback on anxiety and performance in an interceptive task - Harris, David John; Arthur, Tom; Vine, Samuel James; Rahman, Harith Rusydin Abd; Liu, Jiayi; Han, Feng; Wilson, Mark R. (Frontiers in Psychology, 2023)
Introduction Whilst the disruptive effects of anxiety on attention and performance have been well documented, the antecedents to anxiety in motivated performance scenarios are less well understood. We therefore sought to understand the cognitive appraisals that mediate the relationship between pressurised performance situations and the onset of anxiety. Methods We tested the effects of performance pressure and error feedback on appraisals of the probability and cost of failure, the experience of anxiety, and subsequent impacts on visual attention, movement kinematics, and task performance during a virtual reality interception task. Results A series of linear mixed effects models indicated that failure feedback and situational pressure influenced appraisals of the probability and cost of failure, which subsequently predicted the onset of anxious states. We did not, however, observe downstream effects on performance and attention. Discussion The findings support the predictions of Attentional Control Theory Sport, that (i) momentary errors lead to negative appraisals of the probability of future failure; and (ii) that appraisals of both the cost and probability of future failure are important predictors of anxiety. The results contribute to a better understanding of the precursors to anxiety and the feedback loops that may maintain anxious states.